2021
DOI: 10.1021/acsami.0c22558
|View full text |Cite
|
Sign up to set email alerts
|

Improved Thermoelectric Properties of N-Type Mg3Sb2 through Cation-Site Doping with Gd or Ho

Abstract: The success of n-type doping has attracted strong research interest for exploring effective n-type dopants for Mg3Sb2 thermoelectrics. Herein, we experimentally study Gd and Ho as n-type dopants for Mg3Sb2 thermoelectrics. The synthesis, structural characterization, and thermoelectric properties of Gd-doped, Ho-doped, (Gd, Te)-codoped, and (Ho, Te)-codoped Mg3Sb2 samples are reported. It is found that Gd and Ho are effective n-type cation-site dopants showing a higher doping efficiency as well as a superior ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 56 publications
(83 reference statements)
6
21
0
Order By: Relevance
“…[30] Recently, many other cation site substitutions are reported with higher doping efficiency and thermal stability compared to the anion alternatives [10,[12][13][14][15]24,30,[44][45][46][47] (Figure 4). Defect formation energy calculations predict that all of these cation site dopants are expected to substitute the Mg(1) site, [24,[47][48][49][50] while a neutron scattering experiment shows the Yttrium (Y) substitution on the Mg(2) site. [44] Further studies will be required; however, it might be more reasonable to expect the preferential cation substitution on Mg(1) site as the Mg(1) site is more flexible in size compared to Mg(2) as Mg( 1) is a Mg atom residing between [Mg 2 Sb 2 ] À2 slabs.…”
Section: Effectiveness Of Cation Cite Dopingmentioning
confidence: 99%
See 1 more Smart Citation
“…[30] Recently, many other cation site substitutions are reported with higher doping efficiency and thermal stability compared to the anion alternatives [10,[12][13][14][15]24,30,[44][45][46][47] (Figure 4). Defect formation energy calculations predict that all of these cation site dopants are expected to substitute the Mg(1) site, [24,[47][48][49][50] while a neutron scattering experiment shows the Yttrium (Y) substitution on the Mg(2) site. [44] Further studies will be required; however, it might be more reasonable to expect the preferential cation substitution on Mg(1) site as the Mg(1) site is more flexible in size compared to Mg(2) as Mg( 1) is a Mg atom residing between [Mg 2 Sb 2 ] À2 slabs.…”
Section: Effectiveness Of Cation Cite Dopingmentioning
confidence: 99%
“…Possible reasons may be the size difference of Y atom and La atom or the suppression of Mg vacancies with Y [44] ; however, further understanding of the effects of various cation dopants should be important as the potential future work to utilize the positive aspect of cation site doping. In addition, Pr, [48] Nd, [47,53] Tm, [47] Ce, [54] Gd, [49,50] and Ho [49] were reported as the effective dopant at least to control the carrier concentration.…”
Section: Effectiveness Of Cation Cite Dopingmentioning
confidence: 99%
“…Many elements have been reported to be effective donor impurities for Mg 3 Sb 2based materials, such as chalcogen (Te, Se and S) and lanthanides (La, Nd, Pr, etc. ), [10][11][12][13][14][15][16] which can achieve a high electron concentration from 10 19 to 10 20 cm À3 . Poor low-temperature thermoelectric performance usually limits the efficiency of a thermoelectric device.…”
Section: Introductionmentioning
confidence: 99%
“…Polvani et al 32 reported that the zT value increased twofold in p-type Sb 1.5 -Bi 0.5 Te 3 upon pressure tuning. For improving the thermoelectric performance of Mg 3 Sb 2 , optimizing carrier concentration 21,[33][34][35] or tuning carrier scattering mechanism 10,26 have been proved to be effective methods by a plenty of literatures, however, there are few theoretical reports about the method of pressure tuning. Therefore, it is necessary and important to investigate the effect of pressure on the thermoelectric properties of Mg 3 Sb 2 , which can provide signicant guides for the experimental researchers.…”
Section: Introductionmentioning
confidence: 99%